ANALISIS STRATEGI PEMASARAN KONVEKSI AMELIA COLLECTION DALAM MENINGKATKAN VOLUME PENJUALAN - Tenri Esa; Jusri Jusri; Andi Muhammad Irwan (Gapenas Publisher, 2021)
Analysis of the Amelia Collection Convektion Marketing Strategy in Increasing Sales Volume under the guidance of Jusri and Andi Muhammad Irwan. This study aims to determine the position of the Amelia Collection Convektion by looking at its internal and external factors in marketing, as well as to find out what strategies are appropriate for Amelia Collection Convektion to be used in increasing sales volume through internal and external analysis of company. This research was conducted using a qualitative descriptive method which aims to obtain an overview of the company’s internal and external factors. The date collection method in this study used interviews, observation, and documentation methods which were then analyzed using SWOT analysis. From the results of the research which were analyzed using SWOT analysis, it can be seen that the Amelia Collection convection is in the first quadrant position which means strong/opportunity and the right strategy to use is SO strategy (Strengths + Opportunities) or aggressive strategy.